Penerapan Outsorching Rekrutmen terhadap Loyalitas Karyawan pada Bank Syariah Padangsidimpuan - Silviana Batubara; Makhrani Makhrani; Ade Maya Mei Shanty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this research is to find out how much influence the implementation of recruitment outsourcing has on employee performance loyalty at Bank Syariah Mandiri Padangsidimpuan. This research uses a descriptive method with a quantitative approach. The results obtained in this research are (1) there is a significant relationship between the implementation of recruitment outsourcing and employee performance loyalty at Bank Syariah Mandiri Padangsidimpuan; (2) means that the level of relationship between the recruitment outsourcing implementation variable and the employee performance loyalty variable is strong; (3) there is a significant relationship between the variable implementing recruitment outsourcing and the employee performance loyalty variable at Bank Syariah Mandiri Padangsidimpuan; and (4) the application of recruitment outsourcing to employee performance loyalty at Bank Syariah Mandiri Padangsidimpuan based on calculations using the determination test formula obtained a value of 52.42% while the remaining 47.58% was influenced by other factors which were not examined by the research.